2021
DOI: 10.1002/adfm.202108496
|View full text |Cite
|
Sign up to set email alerts
|

2–2 Type PVDF‐Based Composites Interlayered by Epitaxial (111)‐Oriented BTO Films for High Energy Storage Density

Abstract: Quick charge/discharge polymer‐based composites filled with inorganic nanosheets have attracted extensive attention and provided a more efficient way to achieve high energy storage density (U) because of the alleviated agglomeration of fillers and the formation of conduction barriers. However, conductive paths have a chance to extend along out‐of‐plane directions by circumventing the micrometer‐sized nanosheets. Here, large‐sized (111)‐oriented BaTiO3 (BTO) films with outstanding epitaxiality and ferroelectric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
24
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 72 publications
(68 reference statements)
0
24
0
1
Order By: Relevance
“…To further raise the energy storage applicability of multilayer-based composites, Wang et al [247] designed a unique multi-layered structure by embedding large size epitaxial BT films exhibiting high ferroelectricity and oriented in (111) direction into PVDF films (Figure 16(e)) by optimal transfer and hot-pressing process. The fabricated 2-2 type PVDF/BT multilayered device exhibited a high energy storage density of 20.7 J/cm 3 with 67.3 % efficiency at a breakdown field of 690 MV/m for optimum BT layer thickness.…”
Section: Rational Design Of Filler Dispersionmentioning
confidence: 99%
See 1 more Smart Citation
“…To further raise the energy storage applicability of multilayer-based composites, Wang et al [247] designed a unique multi-layered structure by embedding large size epitaxial BT films exhibiting high ferroelectricity and oriented in (111) direction into PVDF films (Figure 16(e)) by optimal transfer and hot-pressing process. The fabricated 2-2 type PVDF/BT multilayered device exhibited a high energy storage density of 20.7 J/cm 3 with 67.3 % efficiency at a breakdown field of 690 MV/m for optimum BT layer thickness.…”
Section: Rational Design Of Filler Dispersionmentioning
confidence: 99%
“…Copyright (2021) American Chemical Society.) (e) Cross-sectional SEM image of the 2-2 type PVDF-based composites interlayered by epitaxial (111) BT films reported by Wang et al[247] and (f) the corresponding energy storage performance. (Reproduced with permission from Ref [247]…”
mentioning
confidence: 99%
“…5 Over 20 J cm −3 has been reported in polymeric composites, whereas the discharging efficiency could hardly exceed 80%. 17 The high energy loss is undesirable for energy storage purpose from either the energy utilization efficiency or the system stability point of view.…”
Section: Introductionmentioning
confidence: 99%
“…A widely employed effective strategy to obtain high a U e is to design topologically structures via combining the merits of different layers, which shows an advantage in balancing the dielectric constant and breakdown strength. , The most used structural design is a sandwich structure, which usually contains dielectric layers with inorganic fillers possessing a high dielectric constant and insulating layers of ferroelectric or linear organic dielectrics. It is reported that the macroscopic interface between the adjacent layers formed the interfacial polarization and inhibits the mobile charges across interfaces, which is beneficial to improve energy-storage performance. , Moreover, the electric field in the nanocomposites would be redistributed because of the different dielectric constants between adjacent layers, which relieves the local electric strength and avoids the premature failure of the dielectric film under an external electric field. , For example, Zhu and Wang prepared multilayer-structured dielectrics composed of the P­(VDF-HFP) matrix and Nd-doped BaTiO 3 nanofillers and reported a three-layered composite films with maximum U e of 25.5 J/cm 3 with a E b of 719.9 MV/m 3 . It is noteworthy that this class of multilayer-structured nanocomposites features the dielectric layer using inorganic fillers to enhance the dielectric response, which leads to mismatched inorganic/organic interfaces that require careful modification.…”
Section: Introductionmentioning
confidence: 99%